Evaluating Performance Through Organizational Commitments: Testing Transactional Leadership and Job Satisfaction In The Public Legal Entity Sector - Angga Saputra Desti; Rahmi Fahmy; Yulihasri Yulihasri (Enrichment : Journal of Management, 2021)
This study aims to examine the effect of transactional leadership style and job satisfaction on employee performance, as well as the mediating contribution of organizational commitment, by using a total sampling technique of 50 employees, then the data analyzed by assisting of SPSS V 26, Mc. Excel, and PLS software 3.3. We found that transactional leadership has a negative but not significant on employee performance, negative and significant on commitment, while job satisfaction has a positive and significant on employee performance and commitment. Organizational commitment has a positive and significant on employee performance. Transactional leadership on employee performance through commitment has a significant negative effect, while job satisfaction on employee performance through commitment has a positive and significant with the total mediation both effects categorized partial mediation.